Village fund management under Law No. 3/2024 and its impact on community welfare in Ciawi District from a siyasah maliyah perspective - Fauzan, Fauzan; Saebani, Beni Ahmad; Tresnayadi, Budi (UIN Sunan Gunung Djati Bandung, 2025)
Community welfare is often a serious topic of discussion in terms of its management. The government has yet to find a glimmer of hope in addressing inequality, despite its continued efforts to find various ways to reduce it. The objective of this study is to analyze the extent of the implementation of village fund allocation management, in accordance with Law No. 3 of 2024 on villages, as well as the fiscal policy review in fulfilling the rights of the residents of Kurniabakti and Pasirhuni villages. The mitigation efforts carried out in Kurniabakti Village and Pasirhuni Village include implementing several development programs related to community welfare. It is hoped that these programs will bring benefits to the community and realize the government's desire to mitigate inequality. The villages of Kurniabakti and Pasirhuni have implemented development programs as part of the government's targets to improve the welfare of the community, with the aim of enhancing the well-being of the people in accordance with the principles of Islamic law (maqasid sharia), which prioritize the greater good and avoid harm. The principles of fiscal policy, which encompass trustworthiness and justice, determine how government officials exercise their authority in accordance with Islamic law, as referenced in the Quran and Hadith. Therefore, the review of fiscal policy is used as an analytical tool in this study in Kurniabakti Village and Pasirhuni Village because the research is deemed consistent with the principles of fiscal policy.